Synthesis and photoinduced switching properties of C7-heteroatom containing push–pull norbornadiene derivatives - Krappmann, Daniel; Hirsch, Andreas (Beilstein Journal of Organic Chemistry, 2025)
We report the synthesis and characterization of heteroatom-incorporated norbornadiene (NBD) derivatives. Push–pull substitution on the 2 and 3 position as well as introduction of oxygen or nitrogen at position 7 of the NBD scaffold have led to the development of a new family of photoswitches. We studied the potential conversion of norbornadiene to quadricyclane (QC) isomers. As main investigation tools, UV–vis and NMR spectroscopy were utilized. We determined significant spectral features of the formed NBD species, including λmax and λonset values, all of which exhibit redshifts compared to their isocyclic counterparts. Additionally, the selected QC isomers were subjected to thermal and catalytic back-conversion studies.
Keywords: heterocycles; molecular solar thermal systems; norbornadiene; photochemistry; quadricyclane